Pemberdayaan Kelompok Tani Dalam Meningkatkan Hasil Panen Melalui Penerapan Teknologi Mesin Pompa Air Berbasis Energi Surya Di Desa Besar Ii Terjun Kecamatan Pantai Cermin Kabupaten Serdang Bedagai - Hermansyah Alam; Luthfi Parinduri; Mahrizal Masri; Zulfadli Pelawi; Helma Widya (Jurnal Masyarakat Indonesia (Jumas), 2024)
The application of solar-based water pump technology in Desa Besar II, Pantai Cermin District, Serdang Bedagai Regency, aims to overcome the irrigation challenges faced by local farmers. This village, which is an agricultural area with great agricultural potential, has experienced a decline in crop yields due to inadequate traditional irrigation systems, especially during the dry season. The application of solar water pump technology is expected to increase irrigation efficiency by utilizing solar energy as a clean and sustainable source of energy. The implementation of this activity includes the installation of a solar water pump system, intensive training for farmer groups on the operation and maintenance of the system, and monitoring and evaluation to assess the effectiveness of the technology. The evaluation results showed an increase in crop yields of 20-30% and improved crop quality, thanks to more consistent irrigation. Positive responses from farmers regarding the ease of use of the technology and the training provided also reflect a significant impact on their independence and welfare. Recommendations for further development include the expansion of this technology and increased technical support in the future.